Diversidade da Mastofauna da Região do Baixo Rio Tocantins, Pará - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2004)
The area bordered by the lower third of the Tocantins River harbors one of the highest concentrations of taxa in the eastern Amazon, and can be considered as one of the best studied Amazonian areas. However, the importance of the role played by this river in the biogeography of mammals in the region is the subject of discussion. Due to the accelerated environmental degradation that it has suffered, this region can be seen as a priority area for conservation in the Brazilian Amazon. This study aims to update knowledge on the diversity of mammal fauna in the Amazonian stretch of the Tocantins River, seeking to help clarify questions related to the zoogeography of the region, and providing empirical bases for the application of conservation strategies in this area. It also verifies the relationship between the banks of the Tocantins River and the Marajó archipelago. Data on the species richness of mammals in the area were collected based on records from the collections of the Museu Paraense Emílio Goeldi, Museu Nacional, and Museu de Zoologia da Universidade de São Paulo, as well as a review of available literature, resulting in a list of species of confirmed and expected occurrence in the region. From the data a matrix was generated that will be used for a parsimony endemism analysis (PAE), which will generate a cladogram to classify the areas according to the sharing of taxa. The expected diversity for the study area is about 182 species, distributed in 38 families and 11 orders. Of these, 91 species have already been confirmed to occur. The PAE matrix is still being analyzed, and will show the relationship between the areas, trying to clarify the importance of the Tocantins River in the biogeography of mammal species. According to current knowledge, two genera of primates (Mico and Callicebus) have their distributions apparently restricted to the left bank of the Tocantins River. One endangered species, Cebus haapori, has a distribution restricted to the right bank. Two other mammal genera had terminal taxa differentiated between the banks of this river. According to the IUCN2003 list of threatened species, there is an overlap between the geographic distributions of 41 species considered to be at risk of extinction and the study area.
Diversity of the Mastofauna of the Lower Tocantins River Region, Pará
Keywords: Biogeografia; Inventários; Rio Tocantins; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA